Structural Racism in Schools: A View through the Lens of the National School Social Work Practice Model. Issue 3 (17th July 2020) - Crutchfield, Jandel; Phillippo, Kate L; Frey, Andy
Abstract: Structural racism—implicitly discriminatory practices and policies that have negative consequences for individuals and groups of color—is a powerful force in contemporary American society, including in our public education system. This article explores the potential for school social workers (SSWers) to address structural racism through the use of the national school social work (SSW) practice model as a tool to guide systemic, ecologically oriented intervention within schools and educational policy spaces. In this article, the authors review data on racial disparities in educational attainment, placement, opportunity, and discipline practices that have led to increased attention to structural racism in schools. They then discuss and describe the national SSW practice model and its suitability for the structural interventions in response to structural racism in schools. Finally, they provide recommendations for how SSWers can respond effectively to this pressing social problem. These recommendations include a list of resources for addressing structural racism.